Reversible Covalent Inhibition of eEF‐2K by Carbonitriles. Issue 16 (15th September 2014) - Devkota, Ashwini K.; Edupuganti, Ramakrishna; Yan, Chunli; Shi, Yue; Jose, Jiney; Wang, Qiantao; Kaoud, Tamer S.; Cho, Eun Jeong; Ren, Pengyu; Dalby, Kevin N.
Abstract eEF‐2K is a potential target for treating cancer. However, potent specific inhibitors for this enzyme are lacking. Previously, we identified 2, 6‐diamino‐4‐(2‐fluorophenyl)‐4H‐thiopyran‐3, 5‐dicarbonitrile (DFTD) as an inhibitor of eEF‐2K. Here we describe its mechanism of action against eEF‐2K, on the basis of kinetic, mutational, and docking studies, and use chemoinformatic approaches to identify a similar class of carbonitrile‐containing compounds that exhibit the same mechanism of action. We show that DFTD behaves as a reversible covalent inhibitor of eEF‐2K with a two‐step mechanism of inhibition: a fast initial binding step, followed by a slower reversible inactivation step. Molecular docking suggests that a nitrile group of DFTD binds within 4.5 Å of the active site Cys146 to form a reversible thioimidate adduct. Because Cys146 is not conserved amongst other related kinases, targeting this residue holds promise for the development of selective covalent inhibitors of eEF‐2K.